Environmental, Social, and Governance (ESG) Performance on the Market Value of Banks in ASEAN - Kurniawan, Kurniawan; Kim, Sung Suk (Enrichment : Journal of Management, 2023)
Several studies have been conducted linking Environmental, Social, and Governance (ESG) to the financial performance of companies. However, there is still a limited amount of research investigating the influence of ESG on the market value of banks listed on the stock exchange in ASEAN countries. Panel regression is employed using historical ESG data and the market value of banks from various stock-exchange-listed banks in six ASEAN member countries (Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam) during the period 2013-2022. The results of this study are expected to provide a better understanding of the influence of ESG factors, specifically on the market value of banks in the banking industry of the ASEAN region. Additionally, this research can also offer valuable information for stakeholders, regulators, and market participants regarding the importance of considering ESG factors in investment decision-making within the banking sector.